Makna lima kode semiotika Roland Barthes dalam dongeng "Vom Fischer und seiner Frau" - Jannah, Syifa Miftahul; Haryati, Isti (Journal of Culture, Literature and Foreign Language Teaching, 2025)
This study aims to describe Roland Barthes' five semiotic codes, which consist of: (1) the hermeneutic code, (2) the semic code, (3) the symbolic code, (4) the proairetic code, and (5) the cultural code found in the fairy tale titled "Vom Fischer und seiner Frau." This research is qualitative and uses a semiotic approach by utilizing Roland Barthes' five semiotic codes theory. The research data consists of lexia found in the fairy tale "Vom Fischer und seiner Frau" from the Brothers Grimm collection of fairy tales from 1812. Data was obtained through the technique of reading and noting. The research instrument is the researcher themselves (human instrument). The validity of the data was obtained through semantic validity. The reliability used is intrarater and interrater reliability. The results of the study indicate that there are five semiotic codes of Roland Barthes and their meanings in the fairy tale "Vom Fischer und seiner Frau" as follows: (1) the hermeneutic code consists of puzzles in the form of questions and answers (revealing the characterization of the fisherman, the fisherman's wife, and the Butt), (2) the semic code involves connotations of the setting, characters and characterization, as well as moral messages (connotations of changing seawater depicting certain atmospheres, connotations of certain elements depicting the characterization of the fisherman and his wife, and connotations of the use of elements in determining moral messages), (3) the symbolic code symbolizes the main theme of the story (greed and simplicity), (4) the proairetic code signifies the consequences of actions that then form the plot (the fisherman's wife's ingratitude leads to the fisherman's loss of patience, and karma), and (5) the cultural code signifies the mythological culture in society, language use, and ethical culture (appealing to mythological creatures, use of hyperbolic language, and the importance of being grateful).